Answer:
A&D
Explanation:
we want to solve the following equation for x:
![\displaystyle ( {2}^(x) - 3) ({2}^(x) - 4) = 0](https://img.qammunity.org/2022/formulas/mathematics/high-school/ym2qb2xi80yux3glmynogykexpohcpiwiy.png)
to do so let
be u and transform the equation:
![\displaystyle (u - 3) (u - 4) = 0](https://img.qammunity.org/2022/formulas/mathematics/high-school/5knci8cpbj16n1at8p3wrsv8ct0pmditiv.png)
By Zero product property we obtain:
![\displaystyle \begin{cases}u - 3 = 0\\ u - 4= 0 \end{cases}](https://img.qammunity.org/2022/formulas/mathematics/high-school/2s4p2rblwv79ixajn9xqsu5fd6amrdgoa3.png)
Solve the equation for u which yields:
![\displaystyle \begin{cases}u = 3\\ u = 4 \end{cases}](https://img.qammunity.org/2022/formulas/mathematics/high-school/evoskr497n1evrn1c5f1bzxjgf7kela9oh.png)
substitute back:
![\displaystyle \begin{cases} {2}^(x) = 3\\ {2}^(x) = 4 \end{cases}](https://img.qammunity.org/2022/formulas/mathematics/high-school/qn0c1ld3wc0baqhuxvotcgvjbi202s71ld.png)
take logarithm of Base 2 in both sides of the both equations:
![\displaystyle \begin{cases} \log_(2) {2}^(x) = \log_(2) 3\\ \log_(2) {2}^(x) = \log_(2) 4 \end{cases}](https://img.qammunity.org/2022/formulas/mathematics/high-school/b5l8wmniz1vctiarppoblx2z7aoj4pc3ah.png)
hence,
![\displaystyle \begin{cases} x_(1) = \log_(2) 3\\ x_(2) = 2 \end{cases}](https://img.qammunity.org/2022/formulas/mathematics/high-school/f8dp39ptr5pic5m1hh9wlhvddtik12i0nm.png)